AGE-RELATED CHANGES IN THE PATHOMORPHOLOGY OF ALCOHOLIC LIVER CIRRHOSIS. (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Alcoholic liver cirrhosis (ALC), a severe consequence of chronic alcohol consumption, exhibits distinct pathomorphological changes influenced by age, impacting disease progression and therapeutic outcomes. This article investigates age- related variations in the histopathological and morphometric features of ALC, focusing on fibrosis severity, hepatocyte degeneration, and inflammatory patterns across different age groups. The study analyzes liver biopsy and autopsy samples from 300 ALC patients, revealing advanced fibrosis (stage F4) in 70% of patients aged >50 years versus 50% in those